Implementasi Pendidikan Inklusif Sebagai Perubahan Paradigma Pendidikan di Indonesia - Winda Fionita; Ely Nurjannah (Jurnal Bintang Pendidikan Indonesia, 2024)
The aim of this research is to provide information about how the implementation of inclusive education as a change in the educational paradigm in Indonesia can be carried out. The method used in this research uses a qualitative method with a literature study approach. Library studies can be defined as a series of activities related to collecting library data, reading and taking notes, and processing research materials. Based on the results of the literature study, the implementation of inclusive education in Indonesia is an important paradigm shift in the education system. This aims to ensure that every individual, including those with special needs, has full access to quality education. There are several steps that can be taken in implementing inclusive education as a change in the educational paradigm in Indonesia, namely, policies and regulations; training and education for educators; inclusive curriculum development; inclusive physical facilities; community education; collaboration between institutions; as well as evaluation and monitoring. So in essence inclusive education is very important to create equality, participation and respect for diversity in the classroom. Even though its implementation is still faced with various challenges and obstacles, the efforts of the government and related stakeholders have produced policies, programs and best practice models in inclusive education. Thus, it is important for the government, educational institutions, teachers and society as a whole to continue to work together and commit to encouraging the implementation of better inclusive education.